The Effect of Quality of Work Life on Organizational Citizenship Behavior Mediated by Work Engagement - Lestari, Indah; Rumijati, Aniek; Lestari, Novi Puji (Universitas Muhammadiyah Malang, 2023)
The purpose of this study was to determine the effect of quality of work life on organizational citizenship behavior through the mediation of work engagement at PT. Dija Jaya Perkasa Mataram City. Research using quantitative methods with the entire population of 65 respondents. The sampling technique uses a total of all employees. Sources of data were collected from distributing questionnaires (primary data). The analysis tool uses a range of scales and path analysis. The results of the scale range on quality of work life are said to be good, organizational citizenship behavior is said to be high, and work engagement is said to be high. The results showed that the quality of work life had a negative and insignificant effect on organizational citizenship behavior; quality of work life has a positive and significant effect on work engagement; work engagement has a positive and significant effect on organizational citizenship behavior; work engagement is able to mediate the relationship between quality of work life variables and organizational citizenship behavior.